Dimethylarginine Dimethylaminohydrolase 2 Regulates Nitric Oxide Synthesis and Hemodynamics and Determines Outcome in Polymicrobial Sepsis. Issue 6 (June 2015) - Lambden, Simon; Kelly, Peter; Ahmetaj-Shala, Blerina; Wang, Zhen; Lee, Benjamin; Nandi, Manasi; Torondel, Belen; Delahaye, Matthew; Dowsett, Laura; Piper, Sophie; Tomlinson, James; Caplin, Ben; et al.
<x xml:space="preserve">Abstract</x> Objective— Nitric oxide is a key to numerous physiological and pathophysiological processes. Nitric oxide production is regulated endogenously by 2 methylarginines, asymmetric dimethylarginine (ADMA) and monomethyl-L-arginine. The enzyme that specifically metabolizes asymmetric dimethylarginine and monomethyl-L-arginine is dimethylarginine dimethylaminohydrolase (DDAH). The first isoform dimethylarginine dimethylaminohydrolase 1 has previously been shown to be an important regulator of methylarginines in both health and disease. This study explores for the first time the role of endogenous dimethylarginine dimethylaminohydrolase 2 in regulating cardiovascular physiology and also determines the functional impact of dimethylarginine dimethylaminohydrolase 2 deletion on outcome and immune function in sepsis. Approach and Results— Mice, globally deficient in Ddah2, were compared with their wild-type littermates to determine the physiological role of Ddah2 using in vivo and ex vivo assessments of vascular function. We show that global knockout of Ddah2 results in elevated blood pressure during periods of activity (mean [SEM], 118.5 [1.3] versus 112.7 [1.1] mm Hg; P=0.025) and changes in vascular responsiveness mediated by changes in methylarginine concentration, mean myocardial tissue asymmetric dimethylarginine (SEM) was 0.89 (0.06) versus 0.67 (0.05) μmol/L (P=0.02) and systemic nitric oxide concentrations. In a model of severe polymicrobial sepsis, Ddah2 knockout affects outcome (120-hour survival was 12% in Ddah2 knockouts versus 53% in wild-type animals; P<0.001). Monocyte-specific deletion of Ddah2 results in a similar pattern of increased severity to that seen in globally deficient animals. Conclusions— Ddah2 has a regulatory role both in normal physiology and in determining outcome of severe polymicrobial sepsis. Elucidation of this role identifies a mechanism for the observed relationship between Ddah2 polymorphisms, cardiovascular disease, and outcome in sepsis.